Output floors in setting bank capital requirements - POP, Adrian; POP, Diana (Journal of Financial Stability, 2025)
We examine various implementation issues related to the calibration of output floors in setting minimum bank capital requirements under the finalized version of the Basel III capital accord. The main raison d’être of output floors is to limit the capital savings enjoyed by large banks due to regulatory arbitrage under the internal model paradigm. We consider regulatory arbitrage through the bank’s incentive to optimize its grading system in order to lower as much as possible the capital requirement given the structure of its asset portfolio in terms of internal ratings and default probabilities. Based on a fictional portfolio of SME loans observed over a full business cycle, we conduct a counterfactual analysis in order to compare the effect of the output floor implemented with respect to two benchmarks: ( i ) a standardized approach calibrated from credit ratings assigned by external rating agencies, as proposed in the finalized version of the Basel III capital accord; and ( ii ) an alternative, more granular, and comprehensive standardized approach benchmark, based on an external grading system that mimics the in-house credit assessment systems used by certain national central banks. Our results show that a more granular, risk-sensitive, benchmark is likely to reduce the effect of the output floor on the minimum capital requirement. We also reveal that output floors exhibit a countercyclical pattern, which is an interesting feature of the mechanism from a macroprudential point of view.